Analisa Faktor – Faktor yang Berhubungan Dengan Tindakan Masyarakat Dalam Pencegahan Penyakit Hipertensi di Wilayah Kerja UPTD Puskesmas Bumi Agung Kecamatan Dempo Utara Kota Pagar Alam Tahun 2021 - Hustrianah; Lilis Suryani; Yusnilasari (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Hypertension is an increase in blood pressure that can trigger strokes, kidney disease and heart attacks. To reduce the risk of cardiovascular disease that can be triggered by hypertension by preventing hypertension. The purpose of this study was to look at the factors associated with the prevention of hypertension. This study uses a quantitative method with a Cross Sectional approach. Statistical test using Chi Square test. Analysis Bivariate analysis was used to find out or see the relationship between the two variables. Chi Square statistical test was used with the largest error rate (level significance) / = 0.05 or 5% and a confidence level of 95%. With the provision that if the value of p > (p > 0.05), the decision is rejected. The hypothesis is rejected, meaning that there is no significant relationship between age, gender, education, knowledge, attitudes, the role of the mass media and the role of family and friends. If the value of p (p 0.05), then the decision of the hypothesis is accepted, meaning that there is a significant relationship on age, gender, education, knowledge, attitudes, the role of the mass media and the role of the family. UPTD Bumi Agung Public Health Center, Pagar Alam City in 2021. Suggestions for health centers are that the Puskesmas should optimize service programs related to elderly services such as the elderly posyandu. As for the next research should examine the incidence of hypertension with different research methods and designs.